Reception of the ombudsman in Malaysia and its application in local universities as an alternative dispute resolution - Mohamad Bahri, Nurwafa Atikah; Amir, Dalila; Abdul Hadi, Khairul Anuar (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Alternative dispute resolution (ADR) has become a popular referred medium due to inherent drawback of the litigation process. One of the ADR methods that is being adopted by most countries worldwide is ombudsman. In Malaysia, the first ombudsman established among higher education institutions was the Universiti Sains Malaysia (USM) Ombudsman Office in 2011. It is the university initiative in ensuring good governance and improving the integrity of the university ecosystem. In the university environment, conflicts among stakeholders; students, staffs, administration, and public are inevitable. The needs of having a confidential, independent, impartial, and informal dispute resolution become an outset for ombudsman to be established in higher education institutions. Each complaint is valuable because it can contribute to the improvement of policies, procedures, existing practices, and the university governance. By applying doctrinal research methodology, this study aims to give an overview of the ombudsman concept and how it can be tailored into an effective dispute resolution medium in universities with special reference to some local universities that practiced ombudsman. This study found that university ombudsman needs to be established as most of the existing dispute resolutions available in the universities are still unable to cater conflicts transparently and independently of the administrative influence like the ombudsman, despite they are resolved by addressing both interests and concerns of the parties in general. This study proposes that detailed and comprehensive legal provisions of university ombudsman to be drafted as the government effort in facilitating the strengthening of the universities management and governance.